Association of SERPINC1 Gene Polymorphism (rs2227589) With Pulmonary Embolism Risk in a Chinese Population - Yue, Yongjian; Sun, Qing; Xiao, Lu; Liu, Shengguo; Huang, Qijun; Wang, Minlian; Huo, Mei; Yang, Mo; Fu, Yingyun (Frontiers in Genetics, 2019)
Background and Aims: Genetic variants in the gene SERPINC1 have been shown to be associated with antithrombin deficiency, which subsequently contributes to the susceptibility to venous thrombosis. However, several other studies have shown conflicting results regarding the association of SERPINC1 gene polymorphisms (rs2227589) with the risk of thrombosis. Hence, in the present study, we conducted a case-control study to further evaluate the association between the variant rs2227589 with antithrombin deficiency in pulmonary embolism (PTE). A pooled systematic analysis also conducted to evaluate the risk of rs2227589 in venous thromboembolism (VTE) among multiple populations. Methods: This case-control study involved 101 patients and 199 healthy controls. The allele frequency of SERPINC1 variant rs2227589 was analyzed by Sequenom assay. Antithrombin anticoagulant activity was detected using an automatic coagulation analyzer. In addition, a pooled systematic analysis on 10 cohorts consisting of 5518 patients with VTE and 8935 controls was performed. Results: In total, 27 (26.7%) PTE subjects were diagnosed as having antithrombin deficiency. Our results showed that antithrombin plasma activity was slightly lower in T allele carriers than in C allele carriers. However, there was no significant correlation between rs2227589 genotype and antithrombin anticoagulant activity. The recessive model showed that rs2227589 was significantly associated (p=0.026) with an increased risk [OR: 2.31, 95% CI (1.09–4.89)] of Chinese PTE. The pooled systematic analysis of all case-control study and meta-analysis showed that rs2227589 polymorphism was associated with an increased risk of VTE in the additive model [OR: 1.09, 95% CIs (1.01-1.18), P=0.029] and dominant model[OR: 1.10, 95% CIs (1.01-1.20), P=0.034]. Conclusions: Our study demonstrated that variant rs2227589 is associated with an increased risk of PTE in a Chinese population, but no correlation with antithrombin anticoagulant activity. However, pooled systematic analysis of multiple populations showed a significant association between rs2227589 and risk of VTE in the additive and dominant genetic model.